Ballads in the style of pat metheny a study of four compositions / Saiful Ridzuan Sharafuddin - Sharafuddin, Saiful Ridzuan (2009)
This work examines the devices found common in the ballad works of the composer, Pat Metheny. Four compositions were analyzed and a comparative study was done with the objective of determining the compositional style or techniques present and common in the ballads. The four compositions are Unity Village, Always and Forever, Never Too Far Away and Letter From Home. A Jazz composition is a complex creation, with a lot of areas of discussion, but the analysis presented will only be consumed with the "fixed" portions of the compositions, which are the composed melody and harmony. A stylistic account is then offered based on the findings to give a better understanding of Pat Metheny's approach to ballads. There is scope for further study on the subject based on wider genres and more works, and the methodology could be modified to fit the objective.